Measurement of residual stresses by X-ray diffraction techniques in MoN and Mo2N coatings deposited by arc PVD on high-speed steel substrate - SARIOĞLU, CEVAT (ELSEVIER SCIENCE SA, 2005)
Polycrystalline MoN and Mo2N films have promising physical and mechanical properties, which made them candidates for wear- and corrosion-resistant coatings and diffusion barriers in microelectronics. The residual stresses in MoN and Mo2N films consist of thermal and growth stresses or intrinsic stress generated during deposition. Residual stresses in the MoN and Mo2N coatings deposited by arc PVD techniques on HSS substrate were measured by XRD using the Rocking and the Fixed Incidence Multiplane (FIM) techniques. Residual stresses measured by both techniques in Mo2N (face center cubic, f.c.c.) and in MoN (hexagonal) films were about 5 and 10 GPa (compressive), respectively. These results indicated that residual stresses in the MoN film was two times greater than the residual stresses in the Mo2N film. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: molybdenum nitride; stress; stress measurement; XRD; coatings; MECHANICAL-PROPERTIES; BIAS VOLTAGE; THIN-FILMS; MOLYBDENUM; MICROSTRUCTURE; TEMPERATURE; TIN